Synthesis and characterization of 0.9PMN-0.1PT powders by the use of a modified columbite precursor - Bruno, J. C. [UNESP]; Cavalheiro, A. A. [UNESP]; Zaghete, M. A. [UNESP]; Cilense, M. [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 2005)
The complex perovskite compound 0.9PbMg 1/3Nb 2/3O 3-0.1PbTiO 3 is one of the most promising relaxor ceramic because the addition of lead titanate increases T m, by about 5°C/mol% from intrinsic T m value for pure PMN (near -7 to -15°C). A Ti-modified columbite precursor was used to prepare PMN-PT powders containing single perovskite phase. This variation on columbite route includes Ti insertion in MgNb 2O 6 orthorhombic structure so that individual PT synthesis becomes unnecessary. Furthermore, effects of Li additive on columbite and PMN-PT structures were studied by XRD to verify the phase formation at each processing step. XRD data were also used for the structural refinement by Rietveld method. The additive acts increasing columbite powders crystallinity, and the amount of perovskite phase was insignificantly decreased by lithium addition. By SEM micrographs it was observed that Li presence in PMN-PT powders leads to the formation of rounded primary particles and for lmol% of additive, the grain size is not changed, different from when this concentration is enhanced to 2mol%.
Keywords: Ceramics; Chemical synthesis; Columbite and rietveld method; PMN-PT; Orthorhombic structure; Perovskite phase; Addition reactions; Ceramic materials; Perovskite; Rietveld method; Synthesis (chemical); Powder metals